Environmental, Social and Corporate Governance (ESG): a bibliometric study of practices that influence corporate market value - Teixeira, Fabiana Sousa Ribeiro (2024)
The results indicated that the majority of article publications occurred in 2023, with three authors per publication, and 65% of these studies provide evidence supporting the relationship between ESG practices and companies' market value. Additionally, 25% of the analyzed articles suggest that there is a relationship, but with certain conditions. Lastly, in 10% of the studies considered, no evidence was found to support the influence of ESG practices on companies' market value.